Environmental Regulation and the Export Dynamics of Energy Technologies - Francesco Crespi; Valeria Costantini (Fondazione Eni Enrico Mattei (FEEM), 2007)
The pollution haven hypothesis affirms that an open market regime will encourage the flow of low technology polluting industries toward developing countries, due to potential comparative advantages related to low environmental standards. In contrast, the hypothesis suggested by Porter and van der Linde claims for a competitive dynamic behaviour by innovating firms, allowing a global diffusion of environmental-friendly technologies. Environmental regulation may represent a relevant mechanism through which technological change is induced. In this way countries subject to more stringent environmental regulations may become net exporters of environmental technologies. This paper provides new evidence on the evolution of export flows of environmental technologies across different countries for the energy sector. Advanced economies, particularly the European Union, have given increasing attention to the role of energy policies as tools for sustaining the development path. The Kyoto Protocol commitments, together with growing import dependence of energy products, have stimulated the attention on the analysis of innovation processes in this specific sector. The analysis uses a gravity model in order to test the determinants and the transmission channels through which environmental technologies for renewable energies and energy efficiency are exported to advanced and developing countries. Our results are consistent with the existence of the Porter and van der Linde hypothesis, where environmental regulation represents a significant component of comparative advantages. What strongly emerges is that the stringency of environmental regulation supplemented by the strength of National Innovation System is a crucial driver of export performance in the field of energy technologies.
Keywords: F18; F21; Q43; Q55; Q56; 330; Environmental Regulation; Trade and Environment; Energy Technologies; Umweltpolitik; Energietechnik; Umweltverträglichkeit; Gravitationsmodell; Theorie